IMPLEMENTASI PERMAINAN KALKULATOR JARI UNTUK MELATIH NUMERASI ANAK USIA DINI DI TK PERTIWI KUALA TUNGKAL - Harianja, Sri Indriani; Kartika, Wafa; Septiani, Nurlaily (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
This research was motivated by the need to develop a mathematics learning approach that is in accordance with the characteristics of early childhood development. The focus of this research is the implementation of finger calculator games as an innovative method in improving numeracy and social interaction of children at the Early Childhood Education (ECCE) level. The main objective of this study was to evaluate the impact of finger calculator games on the development of numeracy skills, understanding of basic mathematical concepts, intrinsic motivation, and social interaction of children in TK Pertiwi Kuala Tungkal. The research method used was qualitative experimental involving 15 early childhood children as participants in Pertiwi Kindergarten. Data was collected through intensive observation, interviews, and analysis of calculator game results. This approach provides a holistic picture of the impact of play on children's development. The observations indicated a significant improvement in the numeracy skills and understanding of basic mathematical concepts of the children. In addition, children's intrinsic motivation towards numeracy activities increased markedly, reflected by the constant enthusiasm during the game sessions. Social interaction among children also improved, with increased courage in sharing ideas and cooperation in completing mathematical tasks. This study concluded that finger calculator games are effective in increasing numeracy and social interaction of children in Pertiwi Kindergarten. The positive results show the potential of play as an engaging learning tool that can be integrated into the ECCE curriculum. The practical implications of this research could form the basis for the development of broader game-based learning approaches in early childhood education institutions.